Metal that Will Not Bend : the National Union of Metal Workers of South Africa, 1980-1995. - Forrest, Kally (Wits University Press, 2011)
In the 1980s there was a surge of trade union power on a scale not previously experienced in South Africa. The National Union of Metalworkers of South Africa (Numsa) was a highly prominent and innovative union in this assertion of muscle and one of Cosatu's most radical affiliates, and its story is one of astonishing achievements as its activities built workers' rights and deeply eroded the apartheid state. Metal that will not bend-a translation of the union's motto Insimbi ayigobi-tells that story by revisiting the formation of the powerful modern day union movement. The trade union movement.